And who says it doesn’t make sense? Drama in third-level language classrooms - Weiss, Anna (SCENARIO: Journal for Performative Teaching, Learning, Research, 2007)
This article examines possible implications of Drama in Education (DiE) used in the third-level language classroom. It is based on a series of lessons that I conducted with university students of German, an analysis of the students’ feedback and my own observations. I argue that the small number of publications on the use of DiE in university teaching should not be interpreted as a signal that drama pedagogy does not have a place at this level; on the contrary, this approach has potential that should be highlighted rather than overlooked. In the first part of the article, I will focus on the theoretical basis of DiE, namely central characteristics, implications for the language classroom, and practical issues regarding the practice of language teaching and learning through drama. In the second part, my practical work will be presented and discussed in more detail. This article examines possible implications of Drama in Education (DiE) used in the third-level language classroom. It is based on a series of lessons that I conducted with university students of German, an analysis of the students’ feedback and my own observations. I argue that the small number of publications on the use of DiE in university teaching should not be interpreted as a signal that drama pedagogy does not have a place at this level; on the contrary, this approach has potential that should be highlighted rather than overlooked. In the first part of the article, I will focus on the theoretical basis of DiE, namely central characteristics, implications for the language classroom, and practical issues regarding the practice of language teaching and learning through drama. In the second part, my practical work will be presented and discussed in more detail.